Acceptability of and experiences with menstrual hygiene cups among adolescent girls and young women aged 15–24 in two communities in Lusaka, Zambia: an exploratory study nested in the Yathu Yathu trial - Melleh Gondwe; Melvin Simuyaba; Mwelwa Phiri; Chisanga Mwansa; Albertus Schaap; Lucheka Sigande; Kwame Shanaube; Sian Floyd; Sarah Fidler; Helen Ayles; Musonda Simwinga; Bernadette Hensen (Reproductive Health)
Abstract Background Menstrual cups could be a sustainable menstrual material for adolescent girls and young women (AGYW) in sub-Saharan Africa. Yathu Yathu was a cluster-randomized trial of community-based delivery of HIV and sexual and reproductive health services to young people in Lusaka, Zambia. Among services available through the intervention were menstrual products, including menstrual cups. We explored knowledge of menstruation and menstrual products, acceptability, and experiences of using cups among AGYW aged 15–24. We share lessons learned on how to distribute cups through community-based strategies to AGYW in urban communities. Methods Through community-based, peer-led spaces (hubs), AGYW could access menstrual products, including pads and menstrual cups. We conducted four focus group discussions, two with AGYW aged 15–19 (n = 9) and 20–21 (n = 8) who had accessed different menstrual products through Yathu Yathu and two with AGYW aged 15–19 (n = 5) and 20–24 (n = 9) who had accessed menstrual cups. Four interviews were conducted with four AGYW (15–19, n = 2; 20–24, n = 2) who had accessed cups, and four with two AGYW who were enrolled in a qualitative cohort. Data were analyzed thematically. Results ‘Surprise’ and ‘fear’ were initial reactions from most AGYW who saw the cups for the first time at Yathu Yathu hubs. Misconceptions that cups cause cancer and fears that they could get stuck in the vagina, cause sore, vagina enlargement, and loss of virginity were raised by AGYW. The desire to try the cup, use an alternative menstrual product and information gained at the hubs facilitated access. Use of the cup was comfortable, and cups were said to be cost-effective and durable. Advantages over pads included: the absence of odor, easy to maintain, and environmentally friendly: “it is hygienic, and it is even easy to maintain”. Challenges included pain, discomfort, and failure to or incorrectly inserting the cup at initial use. When faced with challenges using the cup, AGYW reported going back to the hub for additional information and demonstrations on use. Conclusion Despite concerns, misconceptions and initial challenges, cups were acceptable among AGYW. Free distribution of cups provides an opportunity to address menstrual health challenges among AGYW. However, as a new product, there is need to increase awareness and provide detailed information on use.